Waste Recovery and Management An Approach Toward Sustainable Development Goals - Kumar, Ajay; Kumar, Parveen; Kumar, Ashwini; Mittal, Ravi Kant; Goel, Rajesh (CRC Press/Taylor & Francis Group, 2023)
Sustainable development approaches cannot be met unless waste management is addressed as a priority. Waste Recovery and Management: An Approach Toward Sustainable Development Goals presents a comprehensive examination of environmental pollution and health hazards caused by differing types of waste, its recycling and other e-waste management strategies, and potential political and legal interventions. It also presents the available carbon-recycling methods and investigates how these might be applied to reinforce waste management in both industrialized countries as well as developing and emerging economies. Each chapter includes valuable data and case studies that serve as practical guidance for academicians, researchers, and stakeholders for quantifying the impacts of waste, and for planning integrated solid waste collection and treatment systems, thereby working toward sustainability at a global level. Features: Covers both traditional and new technologies for identifying and categorizing the sources and nature of various types of waste. Provides methods for the safe disposal of municipal solid wastes, plastic waste, bio-medical wastes, hazardous wastes, and e-wastes. Explains practical measures to cover the broad spectrum of everyday applications of waste management for environmental sustainability. Contains a focused discussion of the current scenario and future research directions for different types of waste in each chapter.